Vascular plant diversity in the former Kakhovka Reservoir area: two years after the dam breach (CHORNOMORSKI BOTANICAL JOURNAL, 2026)
Question: What is the composition of vascular plants in the territory of the former Kakhovka Reservoir in the early stages of its overgrowth, and what are the trends for the further development of this ecosystem? Location: Area of the former Kakhovka Reservoir, Kherson, Zaporizhzhia, Dnipropetrovsk oblasts, Ukraine. Methods: The study involved field surveys conducted during seven research trips between June 2023 and October 2025. Structural comparative analysis and phytoindicative assessment were performed to evaluate floristic changes. Data processing, including Pearson's criterion and Kruskal–Wallis tests, was conducted in the R software environment. Nomenclature: Vascular plants species – POWO, families, traits – FloraVeg.EU Results: The vascular plant richness showed a rapid exponential increase, rising from 11 species in June 2023 to 343 species by October 2025. The taxonomic structure stabilized quickly, with Compositae, Poaceae, and Brassicaceae becoming the dominant families already in the first year. A significant shift in life forms and dispersal mode was observed: while the initial stages were domi-nated by annuals and anemochorous species (e.g., Salix spp., Populus nigra), subsequent years saw an increase in perennial herbs and species with zoochorous and autochorous dispersal. Phytoindicative analysis revealed a gradual transition from hygrophytic communities to mesophytic ones as the substrate stabilized, although willow-poplar forests continue to form the structural backbone of the new landscape. Notably, the proportion of alien species (neophytes) peaked at the very first period of observations and then declined, suggesting high resilience of the emerging native communities. The presence of rare species, such as Carex secalina, further underscores the rapid formation of ecosystems with high con-servation value. Conclusions: The studied flora is undergoing rapid development, increas-ingly resembling natural floodplain ecosystems of the Lower Dnieper. The main structural changes occurred within the first three months after the dam breach, followed by a period of stabilization in the proportions of major plant groups.
Keywords: biodiversity, recovery, floodplain ecosystems, functional traits, phytoindication, succession, Ukraine, vascular plants